2018
DOI: 10.1007/s40820-018-0195-3
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembled Bacterial Cellulose/Graphene Oxide Hydrogels with Extremely Enhanced Mechanical Properties

Abstract: Uniform dispersion of two-dimensional (2D) graphene materials in polymer matrices remains challenging. In this work, a novel layer-by-layer assembly strategy was developed to prepare a sophisticated nanostructure with highly dispersed 2D graphene oxide in a three-dimensional matrix consisting of one-dimensional bacterial cellulose (BC) nanofibers. This method is a breakthrough, with respect to the conventional static culture method for BC that involves multiple in situ layer-by-layer assembly steps at the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 45 publications
4
62
1
Order By: Relevance
“…Crystalline structure was analyzed by XRD measurement, and the results are presented in Figure a. Similar to our previous studies, BC shows three obvious peaks at 14.2, 16.6, and 22.8°, which results from the diffractions of the (11¯0), (110), and (200) planes of cellulose I . The calculated crystallinity index ( C I ) of BC is 84.4%, which is comparable to previously reported values .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Crystalline structure was analyzed by XRD measurement, and the results are presented in Figure a. Similar to our previous studies, BC shows three obvious peaks at 14.2, 16.6, and 22.8°, which results from the diffractions of the (11¯0), (110), and (200) planes of cellulose I . The calculated crystallinity index ( C I ) of BC is 84.4%, which is comparable to previously reported values .…”
Section: Resultssupporting
confidence: 86%
“…To obtain BC fabric with uniform structure on the top and bottom layers, the BC pellicle was prepared by the membrane liquid interface culture (MLIC) method, as described previously . As reported in our previous work, the bacterial strain, Komagataeibacter xylinus X‐2, was used.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology shown in Fig. 1b reveals a typical interconnected porous structure of BC, in line with our previous studies [10,11]. As shown in Fig.…”
Section: Morphology and Structuresupporting
confidence: 90%
“…These cell residues as well as other impurities such as organic acids, salts as well as residual sugars and other components in the culture medium should be removed. Although many methods are employed such as washing, centrifugation, filtration, and chemical extraction [4], washing BC with hot NaOH solution is the most commonly used [4][5][6][7][8][9][10][11]. The effect of NaOH treatment on structure and mechanical properties of BC has been reported [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…1a. Figure 1b showed the nanofibrous structure of BC membrane, consistent with our previous work (Luo et al 2018). Figure 1b also revealed that the BC membrane prepared in this work has a high transmittance of 92.7% at 700 nm wavelength.…”
Section: Morphology and Transparency Of Bc Membranesupporting
confidence: 89%